Mapping chromosome neighborhoods - Jeffrey Perkel (BioTechniques)
The discovery of topologically associating domains (TADs) changed the way researchers think about gene expression and chromosome structure. Jeffrey Perkel takes a closer look into these “chromosome neighborhoods.”